(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
Anticorrosive potential of Synsepalum dulcificum leaf extract on the corrosion of mild steel in HCl solution was investigated using chemical technique. The extract inhibited the deterioration of mild steel in HCl solution and the inhibition efficiency increased with increasing concentration of the extract at 30o C. The results obtained showed that inhibition was as a result of the adsorption of the inhibitor molecule onto mild steel surface and the adsorption obeyed Flory-Huggins adsorption isotherm.